2011
DOI: 10.1042/cs20110114
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of the inhibitory effect of atorvastatin on leptin expression induced by angiotensin II in cultured human coronary artery smooth muscle cells

Abstract: Leptin contributes to the pathogenesis of atherosclerosis. Ang II (angiotensin II), a proatherogenic cytokine, increases leptin synthesis in cultured adipocytes. Statin suppresses leptin expression in adipocytes and human coronary artery endothelial cells. However, the effect of Ang II and statin on leptin expression in VSMCs (vascular smooth muscle cells), the major cell types in atheroma, is poorly understood. Thus the aim of the present study was to investigate the molecular mechanism of atorvastatin for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Furthermore, blocking OB-Rs in these car-529 diomyocytes prevented the hypertrophic effects ANG II 530 normally has on these cells suggesting that leptin may 531 mediate effects normally attributed to direct ANG II action 532 (Rajapurohitam et al, 2012). Finally, in human vascular 533 smooth muscle cells, it has been previously found that 534 increased ANG II results in increased leptin protein and 535 mRNA expression (Shyu et al, 2012). Thus, it is not 536 unreasonable to suggest that leptin may be involved in 537 mediating some of the changes in carotid body chemosen-538 sitivity normally attributed to ANG II (Eyzaguirre and 539 Zapata, 1968;Bock, 1980;Gomez-Nino et al, 1990).…”
Section: Fig 2 Fluorescent Photomicrographs Of the Carotid Body Shomentioning
confidence: 94%
“…Furthermore, blocking OB-Rs in these car-529 diomyocytes prevented the hypertrophic effects ANG II 530 normally has on these cells suggesting that leptin may 531 mediate effects normally attributed to direct ANG II action 532 (Rajapurohitam et al, 2012). Finally, in human vascular 533 smooth muscle cells, it has been previously found that 534 increased ANG II results in increased leptin protein and 535 mRNA expression (Shyu et al, 2012). Thus, it is not 536 unreasonable to suggest that leptin may be involved in 537 mediating some of the changes in carotid body chemosen-538 sitivity normally attributed to ANG II (Eyzaguirre and 539 Zapata, 1968;Bock, 1980;Gomez-Nino et al, 1990).…”
Section: Fig 2 Fluorescent Photomicrographs Of the Carotid Body Shomentioning
confidence: 94%
“…In order to measure the production of reactive oxygen species (ROS), an assay using 2′,7′‐dichlorodihydrofluorescein diacetate (DCFH‐DA, Molecular Probes) was performed as previously described . After serum starvation for 48 hr, PASMCs (1 × 10 5 cells) were stimulated by Ang II (10 nM) for 48 hr with or without pretreatment of BNP (1–1,000 nM, 30 min).…”
Section: Methodsmentioning
confidence: 99%
“…In order to measure the production of reactive oxygen species (ROS), an assay using 2 0 ,7 0 -dichlorodihydrofluorescein diacetate (DCFH-DA, Molecular Probes) was performed as previously described. 20,21 After serum starvation for 48 hr, PASMCs (1 Â 10 5 cells) were stimulated by Ang II (10 nM) for 48 hr with or without pretreatment of BNP (1-1,000 nM, 30 min). One group of PASMCs were pretreated with Rp-cGMPS (50 mM, 30 min) before treatment of BNP (1,000 nM, 30 min), followed by stimulation with Ang II (10 nM, 48 hr).…”
Section: Determination Of Intracellular Reactive Oxygen Speciesmentioning
confidence: 99%
“…IL-10 has been found to be over-expressed in liver cancer tissues with AXIN1 and PIK3CA mutations (Boyault et al, 2007), therefore, its down-regulation in HepG2 cells suggests that it is indicative of the inflammatory process specifically related to HCC because it is found in the absence of viral and genetic complications. As regards adipokines, AGT (angiotensin) is produced constitutively and released into the circulation mainly by the liver; it increases the synthesis of LEP (leptin) that plays a key role in regulating energy intake and energy expenditure (Shyu et al, 2012) and, on the other hand, down-regulates NAMPT (Nicotinamide phosphoribosyltransferase) that activates insulin receptor and has insulin-mimetic effects, by lowering the blood glucose and improving the insulin sensitivity (Benigni et al, 2009). Our data are, as expected, consistent with their close inter-correlation, however, their concomitant down-regulation has also been found in liver tissues with HCC associated to other complications such as HBV, HCV, hematochromatosis, and Wilson's disease (Budhu et al, 2006;Chan et al, 2006), thus, these adipokines cannot be used as liver cancer marker.…”
Section: Down-regulated Genesmentioning
confidence: 99%